Hebrew Idioms in the Book of Mormon - Sperry, Sidney B. (Journal of Book of Mormon studies, 1995)
Literal translations of Hebrew idioms are prevalent in the Book of Mormon, as are literal renditions of compound Hebrew prepositions. Parallels can be found in the Old and New Testaments, especially in the Hebrew translation of the Old Testament.